Portable Network Aquisition System using Single Board Computer & GNU/Linux - Md. Mostafijur, Rahman (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 15th - 16th March 2008 at Putra Brasmana Hotel, Perlis.